PEMBERIAN SARAPAN MEMPERCEPAT WAKTU REAKSI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Nayaka Putra, A.A.Ngurah Wisnu; Muliarta, I Made (E-Jurnal Medika Udayana; vol 4 no 11(2015):e-jurnal medika udayana, 2015)
PROVIDING BREAKFAST TO ACCELERATE REACTION TIME OF STUDENTS IN MEDICAL FACULTY UDAYANA UNIVERSITY The busyness owned by the students at this era often makes them forget for breakfast so that decreased the energy intake that causes their rapid fatigue and difficulty concentrating. Test psychomotor reaction time provides a description of the fatigue that occurs in students. This study aims to investigate the influence of breakfast for reaction time of students in Medical Faculty Udayana University. Has carried out the research with treatment by subject design in students of medical faculty udayana university class of 2012. This study used 33 subjects, 17 men and 16 women. The study was conducted first by measuring the students reaction time after lecture without breakfast intervention, then remeasurement the students reaction time after lecture with breakfast intervention. The results showed a significant difference between the reaction time 790.24 ms before intervention, with the reaction time of 590.67 ms after intervention (p = 0.000). The results showed  that breakfast accelerate reaction time.
Keywords: Reaction time; breakfast; energy